The globalization of hate : internationalising hate crime? - Schweppe, Jennifer; Walters, Mark Austin, 1980- (Oxford : Oxford University Press, 2016)
This title brings together internationally acclaimed scholars with researchers, policy makers and practitioners from across the world to critically scrutinise the concept of hate crime as a global phenomenon. It examines whether hate crime can, or should, be conceptualised within an international framework and, if so, how this might be achieved.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 14, 2016).
Keywords: Hate crimes; True Crime